Uji Karakteristik Briket Berbahan Baku Tempurung Kelapa Dengan Perekat Tepung Kanji Berdasarkan Dimensi dan Berat - Ariski, Muhammad Alfandi; Mikhratunnisa, Mikhratunnisa (Universitas Gajah Putih, 2023)
Briquettes are a type of solid formed from materials which then experience hardening according to predetermined quality standards. In Indonesia, the quality standards for briquettes are regulated by SNI 01-62352000. This standard includes provisions that briquettes must have a maximum moisture content of 8%, mass loss when heated to 9500℃ must not exceed 15%, maximum ash content of 8%, and minimum calorific value of 5000 cal/g. This study aims to examine the effect of variations in dimensions and weight of charcoal on coconut shell briquettes with starch adhesive. The test was carried out using a completely randomized design (CRD) with three repetitions. The results showed that dimensions and weight had an effect on the moisture content, ash content, and flammability of the briquettes but had no effect on the crushing index. Briquettes with cubic dimensions and a weight of 300 grams had the highest moisture content (8.65%) and the highest ash content (2.13%). The pyramid-dimension briquettes weighing 100 grams had the lowest moisture content (3.80%) and the lowest ash content (1.38%). The lowest destruction index was found in pyramid briquettes weighing 100 grams (0.248%). In cube briquettes weighing 200 grams, the calorific value is 4998 cal/gram.